2023
DOI: 10.1002/efd2.75
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the nutraceutical profile, chemical composition, and health benefits of jaggery: Updates from recent decade

Abstract: Foods as medicine have been utilized from ancient civilizations and shared from generation to generation as dietary health practices. It provides therapeutic assistance along with nutrition and health benefits. Presently, food products, diet, and individual health are receiving a lot of attention and are in high demand. In this context, jaggery is an important part of food and diet in the rural areas of many regions/countries. It is made up of sugarcane juice and is recognized as a natural source of nutraceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…As a result, food technologists are assessing several less expensive ways for farmers to store Jaggery for an extended period of time.The right packing material should be chosen to protect Jaggery from contamination and moisture gain during storage and transportation in order to prolong the product's shelf life. Due to its low processing, Jaggery has a short shelf life and requires certain storage conditions [10]. The shelf life study of Jaggery packaged under specified packaging is important because it identifies the type of packaging that effectively extends the product's shelf life without loss of its quality.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, food technologists are assessing several less expensive ways for farmers to store Jaggery for an extended period of time.The right packing material should be chosen to protect Jaggery from contamination and moisture gain during storage and transportation in order to prolong the product's shelf life. Due to its low processing, Jaggery has a short shelf life and requires certain storage conditions [10]. The shelf life study of Jaggery packaged under specified packaging is important because it identifies the type of packaging that effectively extends the product's shelf life without loss of its quality.…”
Section: Introductionmentioning
confidence: 99%
“…Jaggery is regarded as a therapeutic sugar in Indian Ayurvedic medicine, used to heal lung and throat infections. In vivo studies reported that a dietary supplement of Jaggery was found to exhibit health benefits [1] Jaggery being a least processed sugar retains phenolics and other phytochemicals with potent biological activities like antioxidant, cytoprotective and anthelmintic activity [2]. The physical and chemical composition of Jaggery as well as its storage environment play a significant role in determining the quality of product.…”
Section: Introductionmentioning
confidence: 99%